The relationship between engagement in co-curricular diversity and civic responsibility: exploring gender differences - Subramaniam, Tilagavati; Tamam, Ezhar; Bolong, Jusang; Waheed, Moniza (AkiNik Publications, 2021)
The amount of outside classroom engagement students gains while in the campus is important to develop their civic responsibility. Developing civic responsibility in the students allows the higher education to fulfil their basic mission which is the preparation of good citizen. The aim of this study is to analyze the relationship between engagement in co-curricular diversity and civic responsibility. Gender differences were also assessed. co-curricular diversity is involvement of student in sports, clubs, debate, drama, student council, volunteerism and other social events (Bowman, 2011; Denson, 2009; Reason, 2013; Shamsudin, Ismail, Al-Mamun, & Nordin, 2014) [5, 10, 17, 19] . Data are obtained through a survey questionnaire to total of 720 respondents from three public research universities in Malaysia. This study employs quantitative method using Spearman correlation and analysis of covariance (ANCOVA). The study found that there are some gender differences in the degrees of participation in co-curricular diversity activities and the development of civic responsibility characteristics. The more exposure student in outside classroom experiences, the more develop student civic responsibility. This study shows that there is small disparity between male and female students and their levels of engagement in activities that may ultimately influence engagement in civic life. Present study suggests University should create more co-curricular diversity opportunities for both genders to avoid disparity.